2000
DOI: 10.1007/pl00010064
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid-Squamous Carcinoma of the Esophagus: Report of a Case

Abstract: We report herein the case of a 69-year-old man with basaloid-squamous carcinoma (BSC) of the esophagus. To the best of our knowledge, this is the 60th case of BSC of the esophagus to be reported in Japan, and a review of the other 59 cases is presented after this case report. In our patient, endoscopic findings revealed a circumferential erosion in the middle intrathoracic esophagus (Im), and a protruding tumor with friable ulceration in the center of the erosion. A biopsy suggested that it was moderately diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 9 publications
0
21
0
2
Order By: Relevance
“…The growth pattern of BSCE is downward and expansive even at an early stage [15] . Superficial BSCE shows a submucosal tumor-like form or polypoid elevation [16,17] .…”
Section: Discussionmentioning
confidence: 97%
“…The growth pattern of BSCE is downward and expansive even at an early stage [15] . Superficial BSCE shows a submucosal tumor-like form or polypoid elevation [16,17] .…”
Section: Discussionmentioning
confidence: 97%
“…Since Yamamoto et al reported the first case of BSC of the esophagus in 1979 [2], approximately 60 cases of BSC have been reported, mainly from Japanese institutions [3][4][5][6][7][8]. The prognosis of BSC is poor, but it remains controversial compared with SCC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zhang et al described that the severe survival rate of BSC was 20% after 2 years for resected 16 patients treated with or without adjuvant chemotherapy [9]. In general, locally advanced BSC is regarded as a therapeutically resistant disease associated with a poor prognosis [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…O paciente apresentou acentuada queda do estado geral e evoluiu para 贸bito com quadro de melena, quatro meses ap贸s o diagn贸stico. , o carcinoma basal贸ide escamoso 茅 mais freq眉ente em homens com idade acima de 40 anos e no ter莽o m茅dio do es么fago tor谩cico 2,4,5,13 . Tais caracter铆sticas sobrep玫em-se 脿s observadas no presente caso, exceto para o local da les茫o, que estava situada no ter莽o distal do es么fago, coincidindo com o referido por Albuquerque et al (2006) .…”
Section: Relato Do Casounclassified
“…Este tipo de neoplasia ocorre com maior freq眉锚ncia no trato aerodigestivo superior, tendo como s铆tios prim谩rios preferenciais a cavidade oral, faringe, laringe, seio piriforme e traqu茅ia 5,8,14 . A incid锚ncia desta les茫o no es么fago 茅 extremamente rara, corresponde a 0,1 a 5% das neoplasias malignas do es么fago 1,6,11,15 .…”
unclassified